RISK ANALYSIS OF CONSTRUCTION WASTE FACTOR IN THE CONSTRUCTION PROJECT OF APARTMENT WESTOWN VIEW SURABAYA - Aushaf Helmi Anwar Ismail; Fadjar Purnomo; Devi Zettyara (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
Construction waste refers to the depletion of resources resulting from activities that incur direct or indirect costs without add value to the final product or construction progress. This research aims to identify and analyze construction waste factors that influence the construction project of Apartment Westown View Surabaya. A quantitative approach through a questionnaire survey was applied, with respondents consisting of workers involved in the project. Data analysis was conducted using linear regression to determine the most influential factors, and the COSO ERM framework was used for risk management. The results revealed that the most influential factors on construction waste are: (1) Owner: X7.1; (2) Consultant: X2.3; (3) Contractor: X4.4; (4) All parties: X2.3. The overall project performance assessment shows: (1) approved cost increments, (2) approved time increments, (3) good quality of project performance, (4) sufficient level of satisfaction with project performance. The estimated risk mitigation costs are: (1) Owner: 2.76%, (2) Consultant: 2.07%, (3) Contractor: 1.96%, (4) All parties: 3.67% compared to contract value. This research offers important insights for construction project stakeholders to identify and mitigate factors that cause waste, with the aim of improving overall project efficiency and performance.